Primary Cutaneous Nocardiosis in a Patient With Nephrotic Syndrome: A Case Report and Review of the Literature. Issue 3 (January 2016) - Chen, Bing; Tang, Jin; Lu, Zeyuan; Wang, Niansong; Gao, Xuping; Wang, Feng
Abstract : Abstract: Nocardia infection is not common in clinical practice and most cases occur as an opportunistic infection in immunocompromised patients. We report a case of primary cutaneous nocardiosis characterized by multiple subcutaneous abscesses due to Nocardia brasiliensis in a patient with nephrotic syndrome undergoing long-term corticosteroid therapy. The patient was diagnosed with nephrotic syndrome 9 months ago, and mesangial proliferative glomerulonephritis was confirmed by renal biopsy. Subsequently, his renal disease was stable under low-dose methylprednisolone (8 mg/d). All of the pus cultures, which were aspirated from 5 different complete abscesses, presented Nocardia . Gene sequencing confirmed that they were all N. brasiliensis . The patient was cured by surgical drainage and a combination of linezolid and Trimethoprim-Sulfamethoxazole. The case highlights that even during the period of maintenance therapy with low-dose corticosteroid agents, an opportunistic infection still could occur in patients with nephrotic syndrome.